(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the concept of data structure, lists play a major role in data distribution. "Java lists are interfaces that can be extended to collection interfaces." Lists can be implemented in two ways: array lists and linked lists. The array list is a class that provides an array of extensible lists of Abstract Data Types (ADTs). Linked lists provide different implementations of the ADT. Different types of linked lists are supported in the data structure, including singly linked lists, double linked lists and circular linked lists. This article deals with the analysis of arrays and linked lists (ie, singly linked lists) by performing operations such as inserting, deleting, and searching, and provides results and distributes data according to time complexity. Determine which is more appropriate and effective. This study uses the C and Python programming languages to analyze comparative studies of the performance differences in the complexity of various linked lists (linear and circular, single and double). This paper also shows execution times in various programming languages. Linked list is a complex data structure, especially Useful in system or application programming. Linked lists dynamically allocate memory; use it to allocate memory in some locations. The runtime is similar to an array, so it is also called dynamic data Structure